PENGARUH PEMBERIAN JUS ALPUKAT (PERSEA GRATISSIMA) TERHADAP PERUBAHAN KONSTIPASI PADA LANSIA DI PANTI TRESNA WERDHA TERATAI KOTA PALEMBANG TAHUN 2016 - Muzakar Muzakar; Bella Audina (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2018)
Database of International US Census Bureau states that 3,857,327 people of Indonesia have complaints of constipation and they just did self treatment. According to the research, fiber plays an important role in defecation with minimum intake of 100 mg/kg/day. The purpose of this study was to determine the effect of avocado juice (Persea gratissima) to constipation change in the elderly in Panti Tresna Werdha Teratai of Palembang City. This research was a quasiexperimental design - pretest and posttest with control. Sample size was 44 people divided into 2 groups, treatment and control group. The sample was taken with purposive technique sampling using inclusion and exclusioncriteria. The results showed that the average frequency of defecation of elderly with constipation increased after the administration of avocado juice. In the treatment group, the average frequency of defecation before the treatment was 0.82 times, and after the treatment the frequency increased to 1.45 times. The analysis of t-dependent test in the treatment group showed that p value was 0.02 (<0.05). On the other hand, there was no significant change in the control group with p value was 0.83 (> 0.05). Based on these results, avocado juice can increase frequency of defecation in elderly who has constipation.